Kill the hen that crows like a cock: animal encounters in Old Yiddish - Idelson-Shein, Iris (Journal of Jewish studies, 2020)
This article focuses on a selection of Yiddish adaptations of well-known European tales, which were produced during the seventeenth and eighteenth centuries. It examines the ways in which these Old Yiddish tales express concerns surrounding Jewish life in Diaspora, by envisioning strange encounters between humans and animals. The article attempts to untangle the complex discursive web of which these animal-encounter tales formed a part, and which connected notions of humanity and animality with those of religion, gender and class. I argue that in their depictions of aberrant animality, these tales drew on the identification of Jews and animals, as well as on the relationship between animals and violence, to grapple with the dialectical relationship between Yiddish literature and its adjacent Hebrew and German libraries.